Las elecciones de 1936 y su anulación - Cobas Corrales, Manuel Efraín (2018)
This article addresses the General Elections of 1936, previously analyzed international, Latin American and national stage that preceded the election, participants movements and political parties and their candidates, the media, the electoral universe, the civil-military relations, results and incidents of the process, and finally the denouement pleaded, votes cast in the election of October 11 of that year, thereby canceling the general elections and the extension of the mandate of the General Oscar R. Benavides illegal until 1939 with full powers to legislate to stop the functions of Congress December 8,1936.